Influence of Activated Charcoal Addition on the Adhesion, Emission, Physical, Mechanical, and Biological Properties of Particleboard - Yuliati Indrayani; Evi Septiani; Dina Setyawati; Yeni Mariani (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
The objective of this study was to evaluate the use of bagasse-activated charcoal for reduced formaldehyde emissions and their effect on the physical, mechanical, and biological properties of particleboard. Activated charcoal was made by carbonizing bagasse at 300°C for 2.5 h, followed by carbon activation using a 0.1M HCl solution for 24 h. Particleboards were made of a mixture of bagasse and wood particles with a ratio of 100:0, 75:25, 50:50, 25:75, and 0:100. The concentrations of activated charcoal used in manufacturing particleboards were 2, 4, and 6% based on the dry weight of the particles. Particleboards were made with a target density of 0.7 g/cm3 and hot-pressed at 140°C for 10 min with a pressure of 35 kg/cm2. The observed parameters were formaldehyde emission levels, physical properties, mechanical properties, and biological properties of particleboards. The results showed that the more activated charcoal added in the manufacture of particleboards decreased formaldehyde emissions of the panel. Based on the SNI 5008.2:2016, the overall formaldehyde emission value of particleboard in this study with activated charcoal is in the F* category. The addition of activated charcoal improved the physical, mechanical, and biological properties of particleboards in terms of increased density, decreased water content, water absorption, and thickness swelling, increased modulus of elasticity, modulus of rupture, internal bonding, and screw withdrawal, as well as increased resistance to termites. The particleboard with the addition of 6% activated charcoal showed better mechanical, physical, and biological properties. All physical and mechanical properties of particleboard met the JIS A 5908-2003 Type 8 standards, except for the modulus of elasticity. Keywords: Activated charcoal, bagasse, biological properties, formaldehyde emission, mechanical properties, particleboard, physical properties